A Case Series of Double Sequence Defibrillation. (3rd July 2016) - Merlin, Mark A.; Tagore, Ammundeep; Bauter, Robert; Arshad, Faizan H.
Abstract: Introduction: Double Sequence Defibrillation or Double Simultaneous Defibrillation (DSD) is the use of two defibrillators almost simultaneously at their highest allowed energy setting to treat refractory ventricular fibrillation (RVF). One set of pads is placed in the Anterior-Posterior position and the other set of pads is placed in the Anterior-Lateral Position. Both defibrillation buttons are pressed simultaneously. We sought to determine ROSC and survival rates in a large EMS system when DSD is routinely utilized for RVF.Method: A retrospective case series was performed of all patients who received DSD from January 1, 2015 to April 30, 2015. During the four month period, we requested physicians to instruct paramedics to use DSD on patients after three refractory episodes of VF. All Advanced Cardiac Life Support (ALS) patients treated by paramedics are discussed via telephone communication with a physician in the system of 100 ALS treated patients per day.Results: From January 1, 2015 to April 1, 2015, a total of 7 patients were treated with DSD. The mean age was 62 (Range: 45–78), with mean resuscitation time of 34.3 minutes before first DSD (Range: 23–48). The mean number of single shocks was 5.4 prior to DSD (Range: 3–9), with a mean of 2 DSD shocks delivered. VF converted after DSD in 5 cases (57.1%). Four patients survived to admission (43%). Three patients survived to discharge with no or minimal neurologic disability (28.6%). The mean Cerebral Performance Category Scale was 3.4 with 1 indicating good cerebral performance and 5 indicating Brain Death.Discussion: The correct amount of energy in joules for VF remains unknown. In this case series, significant patients converted out of VF. The reason for improved VF conversion may be several factors including additional defibrillation vectors, increased energy, more energy across myocardium, and unknown variables. Additional research is underway to determine if routine DSD will result in improved survival compared to standard defibrillation techniques.